2008
DOI: 10.1159/000142690
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Endothelial Progenitor Cells in Patients with ANCA-Associated Vasculitis

Abstract: Background/Aims: Bone marrow-derived endothelial progenitor cells (EPCs) are believed to contribute to endothelial repair after vascular damage. To investigate the potential for microvascular repair in patients with ANCA-associated vasculitis (AAV), we conducted a cross-sectional study determining the number of circulating EPCs in patients with AAV, chronic uremia, atherosclerosis, and in healthy volunteers. Methods: The number of circulating EPCs was determined by colony-forming assay in 41 patients with AAV,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
1
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 31 publications
2
7
1
2
Order By: Relevance
“…The results of our study differed from previous studies [ 25 27 ]. In an earlier study by de Groot et al, AAV patients and HC showed no difference in hematopoietic stem cell numbers [ 26 ].…”
Section: Discussioncontrasting
confidence: 99%
“…The results of our study differed from previous studies [ 25 27 ]. In an earlier study by de Groot et al, AAV patients and HC showed no difference in hematopoietic stem cell numbers [ 26 ].…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, GPA and MPA patients displayed lower proliferative activity of blood-derived eEOCs (lower numbers of colonies formed in culture—CFU assay). This was in line with observations made by Závada and colleagues [14] who showed significantly decreased CFU-ECs (colony-forming unit endothelial cells) in patients with ANCA-associated vasculitis (AAV). The lower percentages of Flk-1 + myelomonocytic cells despite physiological levels of CD133 + /Flk-1 + myelomonocytic cells might result from a general defect of endothelial differentiation which possibly not only involves de novo generation of eEOCs in the bone marrow but also further differentiation of circulating CD133 + /Flk-1 + cells into Flk-1 + myelomonocytic cells.…”
Section: Discussionsupporting
confidence: 92%
“…The fact that eEOC regeneration is impaired in GPA (and MPA) patients, an observation also made by other investigators [14], combined with the apparently increased antibody binding to PR3 in cells with endothelial properties potentially indicates a pathophysiological role for proteinase 3 in mediating suppression of endothelial-type cells.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Both these EPC parameters, however, increased after the institution of immunosuppressive therapy and disease remission in GPA patients. Závada et al confirmed the observation of Holmen et al of low EPC-CFU in adults with AAV, particularly in uraemic patients; but in contrast to the study of de Groot et al found that neither institution of treatment nor entering remission increased the number of EPC-CFU [ 47 ]. In a separate study the same group went on to demonstrate that patients with AAV who had low EPC-CFU at first presentation had significantly higher rates of early disease relapse, for the first time suggesting that EPC levels might be important prognostically in AAV [ 48 ].…”
Section: Discussionmentioning
confidence: 75%